92.4k views
1 vote
Please help me, tysm if you do

Please help me, tysm if you do-example-1
User Cymric
by
5.7k points

1 Answer

6 votes

Answer:

No solution

Explanation:

7( r - 2 ) - 9(r - 1) = 3 ( 5 - r ) + ( r - 8 )

Distribute 7 through the parentheses

7r - 14 - 9(r - 1 ) = 3( 5 - r ) + ( r - 8)

Distribute -9 though the parantheses

7r - 14 - 9r + 9 = 3(5 - r ) + ( r - 8)

Distribute 3 through the parantheses

7r - 14 - 9r + 9 = 15 - 3r + r - 8

When there is (+) in front of an expression in parentheses, the expression remains the same

7r - 14 - 9r + 9 = 15 - 3r + r - 8

Collect like terms

7r - 9r - 14 + 9 = 15 - 3r + r - 8

-2r - 14 + 9 = 15 - 3r + r - 8

Calculate

-2r- 5 = 15 - 3r + r - 8

Subtract the number

-2r - 5 = 7 - 3r + r

Collect like terms

-2r - 5 = 7 - 2r

Cancel equal terms on both sides of the equation

- 5 = 7

The statement is False for any value of X.

Hence, there is no solution.

Hope this helps...

Good luck on your assignment...

User Nika Kasradze
by
5.2k points